A new live‐cell biobank workflow efficiently recovers heterogeneous melanoma cells from native biopsies. Issue 5 (May 2015) - Raaijmakers, Marieke I. G.; Widmer, Daniel S.; Maudrich, Melanie; Koch, Tabea; Langer, Alice; Flace, Anna; Schnyder, Claudia; Dummer, Reinhard; Levesque, Mitchell P.
Abstract Fibroblast contamination can make establishing primary melanoma cell cultures from native biopsies a major challenge, due to fibroblasts overgrowing the melanoma cells. Standard protocols therefore enrich for highly proliferative melanoma cells that grow well in vitro but may not represent the full range of in vivo tumor heterogeneity. Here we apply conditional methods that more effectively retrieve melanoma cells by differential trypsinization or by inducing fibroblast senescence through contact inhibition, serum starvation or deprivation of adhesion. Simple mixing experiments of melanoma and fibroblast cells demonstrated the efficacy of the new protocols in retrieving slow‐growing melanoma cells. Applying our protocols to 20 cultures that had failed to grow by conventional methods, we could retrieve 12 (60%) validated melanoma cell cultures. Further application of the protocols in the live‐cell biobank of 124 early passage cultures significantly improved recovery rates from 13% using standard protocols to 70% overall for the new workflow.